Analisis Gaya Bahasa Metafora Pada Lirik Lagu Karya LiSA - Annisa Putri; Meira Anggia Putri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2021)
Song is a literary work that is enjoyed by all people, from young people to adults. In the song lyrics, there are many language styles, especially metaphorical styles. Metaphorical language style is an implicit comparative language style. One of the functions of using metaphors in writing song lyrics is to add beauty to the lyrics. Japanese songs are one of the most popular songs by Japanese students or learners, anime enthusiasts and the general public. LiSA is one of the popular Japanese singers whose songs are widely enjoyed. In this study, researchers analyzed the metaphorical language style of LiSA's song lyrics. This study aims to determine the types and meanings of metaphors in LiSA's song lyrics. This type of research is qualitative research with descriptive methods. The data in this study are in the form of phrases containing metaphors in the lyrics of LiSA's songs. The source of the data taken is the lyrics of a song by LiSA which is an anime soundtrack consisting of 8 songs including Adamas, Catch the Moment, Datte Atashi no Hero, Gurenge, Rally Go Round, Rising Hope, Shirushi, and Unlasting. This study uses the theory of Stephen Ullmann. Based on the results of the study, there were 4 types of metaphors, namely anthropomorphic metaphors with 9 data, synesthetic metaphors with 9 data, abstract metaphors with 22 data, and animal metaphors with 2 data. Besides that, there are different meanings in each metaphorical expression.